2003
DOI: 10.1038/sj.npp.1300228
|View full text |Cite
|
Sign up to set email alerts
|

Manipulations During the Second, but not the First, Week of Life Increase Susceptibility to Cocaine Self-Administration in Female Rats

Abstract: We compared the effects of manipulations during week 1 vs week 2 of life on the propensity to self-administer cocaine. Pups received daily subcutaneous saline injections, were handled briefly, or remained undisturbed during their respective treatment periods. Animals handled during the second week of life exhibited increased locomotor response to novelty when tested on postnatal day (PND) 48, compared to all other groups. Rats were implanted with jugular catheters on PND 70 and then given the opportunity to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 92 publications
(100 reference statements)
1
20
0
Order By: Relevance
“…With cocaine self-administration, MS15 male and female rats fail to acquire cocaine self-administration with a unit dose (0.0625 mg/kg per infusion) that supports self-administration in controls and MS180 rats . Further, a protective effect of brief maternal separation against cocaine selfadministration is obtained in MS10 males receiving the separation during the first postnatal week, whereas MS10 females separated briefly during the second, but not the first, postnatal week self-administer more cocaine (Flagel et al, 2003). Thus, sex-and timedependent differences exist in the protective effect of brief maternal separation.…”
Section: B Social Influencesmentioning
confidence: 84%
“…With cocaine self-administration, MS15 male and female rats fail to acquire cocaine self-administration with a unit dose (0.0625 mg/kg per infusion) that supports self-administration in controls and MS180 rats . Further, a protective effect of brief maternal separation against cocaine selfadministration is obtained in MS10 males receiving the separation during the first postnatal week, whereas MS10 females separated briefly during the second, but not the first, postnatal week self-administer more cocaine (Flagel et al, 2003). Thus, sex-and timedependent differences exist in the protective effect of brief maternal separation.…”
Section: B Social Influencesmentioning
confidence: 84%
“…Different effects of drugs of abuse have been observed after different conditions of separation. These effects have included alterations in cocaine self-administration (Flagel et al 2003;Matthews et al 1999), cocaine-induced sensitization (Li et al 2003), conditioned place preference for amphetamine (Campbell and Spear 1999), ethanol preference and effects of antidepressants (Huot et al 2001;Ploj et al 2003), responses to morphine (Kalinichev et al 2001(Kalinichev et al , 2002(Kalinichev et al , 2003, conditioned appetitive cues (Matthews et al 1996) and behavioral responses to stress (Meaney et al 1996). In addition, several neurochemical alterations in the dopamine mesolimbic system have been reported that may underlie some of the observed behavioral changes (Brake et al 2004;Hall et al 1999;Meaney et al 2002;Ploj et al 2003).…”
Section: Introductionmentioning
confidence: 94%
“…However, this highly-plastic neuronal environment makes the brain highly susceptible to pathological insult (Bondi et al, 2014;Enoch, 2011;Meyer-Lindenberg and Tost, 2012;O'Connor and Cryan, 2014) including psychological stress which has been well established as predisposing individuals to addictive disorders later in life (De Bellis, 2002;Enoch, 2011;Koob, 2008). Indeed, preclinical studies have demonstrated psychological stress induced early in life can affect reward-function in adulthood; both increasing rewardinduced behavioural-reinforcement (Flagel et al, 2003;Kosten et al, 2000;Matthews et al, 1999) and decreasing reward intake, possibly through anhedonia (Martini and Valverde, 2012;Matthews et al, 1999;Silveira et al, 2010). Thus, a need to clarify the mechanisms by which exposure to a psychological stress can alter drug-intake in adulthood remains.…”
Section: Introductionmentioning
confidence: 96%